Systematic Literature Review: Role Playing dan Storytelling dalam Matematika SD untuk Meningkatkan Berpikir Kritis dan Pemecahan Masalah - Tri Wulandari; Alice Felicia Azaria Hia; Resyarusyda Parandrengi (Lembaga Yasin AlSys, 2026)
Critical thinking and mathematical problem-solving abilities are essential competencies that need to be developed from elementary school to support 21st-century learning. However, various evaluation results indicate that these abilities remain relatively low among some Indonesian students, making more innovative, contextual, and participatory learning strategies necessary. This study aims to analyze the effectiveness of role playing and storytelling methods in improving elementary school students’ critical thinking and mathematical problem-solving abilities. This study used the Systematic Literature Review (SLR) method by analyzing seven relevant research articles published between 2021 and 2026. The review process was conducted through the stages of identification, selection, evaluation, and synthesis of articles that met the inclusion criteria. The results of the review show that role playing and storytelling methods can improve students’ critical thinking skills, problem-solving abilities, active participation, learning motivation, and understanding of mathematical concepts. Role playing provides interactive learning experiences through simulation and contextual problem solving, while storytelling helps students understand mathematical concepts through storylines that are closely related to everyday life. The effectiveness of the two methods is influenced by the quality of instructional design, the use of supporting media, teachers’ competence in facilitating learning, and student characteristics. The conclusion of the study affirms that role playing and storytelling can be used as innovative learning strategies to improve the quality of mathematics learning in elementary schools. These findings imply the importance of developing more contextual, active, and meaningful mathematics learning designs to strengthen students’ critical thinking and mathematical problem-solving competencies.